2009
DOI: 10.1109/jmems.2009.2025552
|View full text |Cite
|
Sign up to set email alerts
|

A Model for Electrostatic Actuation in Conducting Liquids

Abstract: This paper presents a generalized model that describes the behavior of micromachined electrostatic actuators in conducting liquids and provides a guideline for designing electrostatic actuators to operate in aqueous electrolytes such as biological media. The model predicts static actuator displacement as a function of device parameters and applied frequency and potential for the typical case of negligible double-layer impedance and dynamic response. Model results are compared to the experimentally measured dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
20
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 32 publications
2
20
0
2
Order By: Relevance
“…1 Recently it has been shown that the stable actuation range can be extended by adding an electret layer to the gap 2 or by operating in a high-dielectric fluid medium with relatively thick low-dielectric solid insulating layers on the electrodes. 3,4 Electrostatic actuation in highdielectric media requires ac drive signals at frequencies f at least on the order of the critical actuation frequency f c to prevent electrode polarization and electrolysis, [5][6][7] but offers the advantage of lower actuation voltages, and is particularly important to microfluidic and bioMEMS development where it is desirable to integrate actuators into aqueous solutions and other conductive fluids. [8][9][10][11][12] For simplicity and to minimize the applied potential required for actuation, most applications of electrostatic actuators in conductive media have been operated in the high frequency limit, viz.,…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1 Recently it has been shown that the stable actuation range can be extended by adding an electret layer to the gap 2 or by operating in a high-dielectric fluid medium with relatively thick low-dielectric solid insulating layers on the electrodes. 3,4 Electrostatic actuation in highdielectric media requires ac drive signals at frequencies f at least on the order of the critical actuation frequency f c to prevent electrode polarization and electrolysis, [5][6][7] but offers the advantage of lower actuation voltages, and is particularly important to microfluidic and bioMEMS development where it is desirable to integrate actuators into aqueous solutions and other conductive fluids. [8][9][10][11][12] For simplicity and to minimize the applied potential required for actuation, most applications of electrostatic actuators in conductive media have been operated in the high frequency limit, viz.,…”
mentioning
confidence: 99%
“…Now consider an applied sinusoidal drive signal V͑t͒ = V a sin͑2ft͒. The solution to Kirchoff's laws gives 7 V l_rms V rms = ͱ…”
mentioning
confidence: 99%
“…However, there has been recent, quite successful, work extending AFM based dielectric measurements to the liquid electrolyte environment. [39][40][41][42][43][44] Properties like charge screening dynamics and electrochemical processes, surface potential of the sample and a full characterization of the electrical double layer at the solid-liquid interface have also been measured. More details of these techniques and the problems encountered are discussed in Sec.…”
Section: Capacitive Measurements In Liquidsmentioning
confidence: 99%
“…As discussed below, various studies have recently been conducted to measure the charge, surface potential, dielectric constant, Stern potential, Debye length and other electrical surface properties in solution. 39,42,[61][62][63] Key to recent advances are the studies carried out by Sounart et al and Panchawagh et al 41,64 on the electromechanical stability of passivated parallel plate electrostatic actuators in conductive dielectric media. They show that by appropriately choosing the frequency of the AC signal one can control the forces between the various components of the actuator.…”
Section: Capacitive Measurements In Liquidsmentioning
confidence: 99%
See 1 more Smart Citation